2017
DOI: 10.1515/johr-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

24-Epibrassinolide Restores the Synthesis of Proteins and Amino Acids in Brassica juncea L. Leaves Under Imidacloprid Stress

Abstract: Pesticides are applied to protect crops from a variety of insect pests but their application cause toxicity to plants that results, among others, in reduction of protein as well as amino acid contents. The present study is aimed at observing the effect of seed pre-soaking with 24-epibrassinolide (EBL) on the protein and amino acid content in the leaves of Brassica juncea L. grown in soil that is amended with pesticide imidacloprid (IMI). Soil amendment with IMI resulted in a decrease in the contents in leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 27 publications
0
1
0
2
Order By: Relevance
“…The results revealed that all the three tested OPs retarded elongation of roots, increased MDA, H 2 O 2 and NO, while exogenous 24-EBL markedly decreased the accumulations of H 2 O 2 , NO and MDA vis-a-vis upregulating the expression of genes associated with antioxidant and detoxification systems. In case of pesticide stress, 24-EBL maintained the optimum synthesis of proteins and amino acids in Brassica juncea L. plants [71]. They applied 24-EBL (100 nM) via the seed presoaking treatment to study the changes in the synthesis of protein and amino acid contents grown under im-idacloprid (IMI)challenged environment.…”
Section: Role Of Brassinosteroidsmentioning
confidence: 99%
“…The results revealed that all the three tested OPs retarded elongation of roots, increased MDA, H 2 O 2 and NO, while exogenous 24-EBL markedly decreased the accumulations of H 2 O 2 , NO and MDA vis-a-vis upregulating the expression of genes associated with antioxidant and detoxification systems. In case of pesticide stress, 24-EBL maintained the optimum synthesis of proteins and amino acids in Brassica juncea L. plants [71]. They applied 24-EBL (100 nM) via the seed presoaking treatment to study the changes in the synthesis of protein and amino acid contents grown under im-idacloprid (IMI)challenged environment.…”
Section: Role Of Brassinosteroidsmentioning
confidence: 99%
“…Esse metal, quando presente no solo, pode agir diretamente no embrião da semente ou no endosperma, atuando nas ligações -SH (grupamentos tióis das células), formando ligações -S-Hg-S-. Tal modificação na conformação molecular afeta o desenvolvimento do embrião, visto que esses tecidos possuem muitas dessas ligações-SH (TOMESCU et al 2017;SHARMA et al 2017SHARMA et al , 2018SOARES et al 2019).…”
Section: A Toxidez Do Mercúrio E Estresse Oxidativo Nas Plantasunclassified
“…Na semente, o Hg age diretamente no embrião ou no endosperma, interagindo rapidamente com os grupamentos tióis das células (ligações -SH). Essa modificação afeta o desenvolvimento do embrião, uma vez que seus tecidos são ricos nesse tipo de ligação (SHARMA et al, 2017;TOMESCU et al, 2017;HANDA et al, 2018;KOHLI et al, 2019;SHAHZAD et al, 2018;SOARES et al, 2019).…”
Section: Introductionunclassified